PEMANFAATAN MEDIA SOFTWARE TRACKER UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI IMPULS DAN MOMENTUM DI SMKN 1 SOREANG - Furi Chorina Agustin; Yudi Dirgantara; Ade Yeti Nuryantini (UIN Sunan Gunung Djati Bandung, 2017)
This study originated from the lack of utilization of learning media during the learning process. Teaching methods used by teachers are less varied so that learners are only trained in cognitive abilities only while for high-level thinking skills such as critical thinking ability is still low. One alternative that can be done to improve the skills of critical thinking is to utilize the Software Tracker media. This study aims to determine the improvement of critical thinking skills of learners through the use of Software Tracker media on the material impulse and momentum. The research method used is Pre-Experiment with design One-Group Pretest-Posttest Design. The sample of this research using Purposive Sampling technique. The research instrument used in this research is the critical thinking skills of the students of impulse material and momentum to measure the critical thinking ability of learners. The data analysis technique uses normality test, and t test to normalized n-gain value from pretest and posttest value of learners using Microsoft Excel. The results showed that the critical thinking skills of learners increased after utilizing the Software Tracker media during learning. The result of this research is proved from the significant value of ttable test of 1.691 while t count is 24.53 which means H0 is rejected and Ha accepted. The results of this study indicate that the use of Software Tracker media on the material impulse and momentum have a positive impact on improving the critical thinking skills of learners.